Consumers' perception of risk towards artificial intelligence technologies used in trade: A scale development study - Pinar Aytekin; Florina Oana Virl\~anut\~a; Huseyin Guven; Silvius Stanciu; Ipek Bolakca (Amfiteatru Economic Journal, 2021)
In today's digitalizing world, internet, mobile technologies, nanotechnologies and learning algorithms continue to develop and gain essential places in our lives. The use of artificial intelligence in wholesale and retail trade enable better analysis of customer requests and the development of effective marketing strategies. However, although these cutting-edge technologies provide significant advantages to businesses, some risks may arise as these technologies continuously develop, and it eventually becomes harder to control the pace of development. Many famous scientists and entrepreneurs are worried that artificial intelligence could have negative consequences for humanity if it does not develop safely, and they suggest that urgent measures need to be taken as they believe that it may pose a significant threat to humanity. The starting point of this study is to learn the point of view of consumers on this technology, as well as scientists or entrepreneurs. The purpose of this study is to determine how consumers perceive these risks. In this direction, the literature focused on the issues related to artificial intelligence technologies in trade was examined. In light of the information obtained from the literature, the Artificial Intelligence Technologies Used in Trade Risk Perception Scale (AITUTRPS) was developed.
Keywords: D81; L81; M21; 330; artificial intelligence; trade technique; risk perception; scale development